2015
DOI: 10.5539/elt.v8n7p46
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Teachers’ Job Satisfaction and Their Attitudes towards Students’ Beliefs and Motivation

Abstract: Many studies have been done in the developed countries due to the importance of job satisfaction; however, only a limited number of studies have been conducted on teachers' job satisfaction in Iran. This study is an attempt to investigate the relationship between teachers' job satisfaction and their attitudes towards students' beliefs and motivation.To this end, both qualitative and quantitative research methods including interview protocols and questionnaire were utilized. To collect data, in the quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Teachers' self-efficacy (TSE) has called the attention of researchers and practitioners alike since it has been identified to be in a direct relationship between teachers' level of self-confidence and students' achievement of academic goals (Tschannen-Moran and Hoy, 2001;Caprara et al, 2006;Nie et al, 2008;Klassen and Chiu, 2010). Other studies have confirmed that self-efficacy influences directly and positively on teachers' job satisfaction, developing a workforce with capabilities to create a successful learning process (Canrinus and Helms-Lorenz, 2011;Collie et al, 2012;Karabiyik and Korumaz, 2014;Skaalvik and Skaalvik, 2014;Dipasupil et al, 2015;Salehi and Taghavi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Teachers' self-efficacy (TSE) has called the attention of researchers and practitioners alike since it has been identified to be in a direct relationship between teachers' level of self-confidence and students' achievement of academic goals (Tschannen-Moran and Hoy, 2001;Caprara et al, 2006;Nie et al, 2008;Klassen and Chiu, 2010). Other studies have confirmed that self-efficacy influences directly and positively on teachers' job satisfaction, developing a workforce with capabilities to create a successful learning process (Canrinus and Helms-Lorenz, 2011;Collie et al, 2012;Karabiyik and Korumaz, 2014;Skaalvik and Skaalvik, 2014;Dipasupil et al, 2015;Salehi and Taghavi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Stephens and Fish (2010) reported that special needs educators experienced high levels of job satisfaction. In a related study, Salehi, Taghavi and Yunus (2015) explored the relationship between teachers' job satisfaction and their attitudes towards students' beliefs and motivation among English teachers in Iran. The study adopted both qualitative and quantitative research methods in data collection and analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that the teachers' attitude toward teaching profession is heavily influenced by management and qualification. Salehi, Taghavil, and Yunus (2015) explored the relationship between Iranian EFL teachers' job satisfaction and their attitudes toward students' beliefs and motivation in a study with the participation of 340 teachers working in language institutes in Isfahan. They concluded that there is a positive significant relationship between teachers' job satisfaction and their attitudes toward students' motivation and beliefs.…”
Section: Previous Studiesmentioning
confidence: 99%